2019
DOI: 10.1111/are.14074
|View full text |Cite
|
Sign up to set email alerts
|

Use of neem oil ( Azadirachta indica) to control caligid copepod infestation on Asian seabass ( Lates calcarifer )

Abstract: Asian seabass (Lates calcarifer) culture in marine cages have been developed rapidly in Malaysia. The high intensity of culture might facilitate several disease infection including caligid infestation. This study was conducted to evaluate the effect of neem oil (Azadirachta indica) against caligid parasites on seabass. The prevalence and clinical pathogen of Caligus infection has been described through a sampling of 150 fish from floating cage at different cultured periods. Acute toxic tests with different con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Similarly, the methanol extracts of Allium sativum (Amaryllidaceae, garlic) (600 µg/mL) were tested against the aquatic leech Limnatis nilotica (Hirudinidae) and took 144.55 min for total mortality [35]. The essential oil of A. indica was applied against a crustacean parasite Caligus (Caligidae) infestation on the Asian seabass Lates calcarifer (Latidae) and showed a 100% mortality of Caligus within 5760 min (96 h) at a rate of 10 ppm [21]. The extract of Artemisia annua (Asteraceae, aromatic herbaceous plant, Sweet Annie) was reported to be effective in 30 to 180 min against monogenean parasites of the cultured airbreathing catfish Heterobranchus longifilis at concentrations ranging from 50 to 200 mg/L [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the methanol extracts of Allium sativum (Amaryllidaceae, garlic) (600 µg/mL) were tested against the aquatic leech Limnatis nilotica (Hirudinidae) and took 144.55 min for total mortality [35]. The essential oil of A. indica was applied against a crustacean parasite Caligus (Caligidae) infestation on the Asian seabass Lates calcarifer (Latidae) and showed a 100% mortality of Caligus within 5760 min (96 h) at a rate of 10 ppm [21]. The extract of Artemisia annua (Asteraceae, aromatic herbaceous plant, Sweet Annie) was reported to be effective in 30 to 180 min against monogenean parasites of the cultured airbreathing catfish Heterobranchus longifilis at concentrations ranging from 50 to 200 mg/L [36].…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous extract of the plant leaf at a concentration of 150 mg/l has been reported to be effective against the pathogenic infection caused by Citrobacter freundii in tilapia [19]. The essential oils of A. indica have been reported to have an antimicrobial property against Enterococcus faecalis, Aerococcus viridans, Pseudomonas aeruginosa, Proteus mirabilis and Escherichia coli and an antiparasitic activity against caligid parasites on seabass [20,21]. The data have revealed that A. indica extracts are toxic to over 400 species of insect pests, some of which have developed resistance to chemically prepared pesticides [15,22].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising medicinal plants is the Neem Azadirachta indica , a broad pharmacological and environmentally friendly compound [ 6 , 7 ]. The proficiency of A. indica has been successfully assessed to control caligid copepod infestation on Asian Sea bass ( Lates calcarifer ) [ 8 ]. freshwater ( Argulus bengalensis) [ 7 ] , and the overpopulation of copepods in cultured Nile tilapia ( Oreochromis niloticus ), and African catfish ( Clarias gariepinus) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several herbal and synthetic products are known to inhibit reproductive growth of the fish (Khalil et al, 2014;Liao et al, 2014). Neem oil has endocrine disruption (Kaur et al, 2020;Narayanaswamy & Mohan, 2012), antibacterial and antiparasitic (Khoa et al, 2019;Swathy et al, 2018) properties well reported in fish.…”
Section: Introductionmentioning
confidence: 99%